An Efficient Electrochemical Polishing Method with Planarization Ability Employing Solid and Liquid Electrolytes. Issue 6 (1st June 2022) - Zhang, Chao; Zhou, Ping; Yan, Ying; Guo, Dongming
Abstract : Stress-free polishing is the most potential machining method for high quality surfaces without surface defects. Traditional electrochemical polishing (L-ECP) is immersed in a liquid electrolyte to realize stress-free polishing. However, due to the limitation of its polishing principle, the electrochemical polishing process cannot improve the surface shape accuracy of the workpiece so far. In this work, a new method solid-liquid electrolyte electrochemical polishing (SL-ECP) for electrochemical polishing assisted by a solid electrolyte polishing pad is proposed. Power spectral density (PSD) of the profile of polished surfaces were compared, and it was found that the low-spatial-frequency error was reduced by contacting the flat solid electrolyte surface with the workpiece surface. After SL-ECP, the roughness S a of the workpiece decreased from the initial 82.83 nm to 2.92 nm (10 μm × 10 μm), and the peak-to-valley value of the entire workpiece surface decreased from the initial 16.39 μm to 1.81 μm. And the material removal rate of SL-ECP was 35 times that of L-ECP using the same liquid electrolyte. This study not only proposes an efficient stress-free polishing method for high-quality surfaces, but also contributes to further understanding of the mechanism of electrochemical polishing.